Pengaruh Kualitas Pelayanan dan Nilai Pelanggan Terhadap Kepuasan Pelanggan Dengan Kepercayaan Sebagai Variabel Moderasi: Studi pada Peserta Magang Mandiri Digital Marketing PT Satukelas Adhyapana Nusantara di Jakarta - Tri Puji Rahayuningsih; Mulyono Mulyono; Dian Candra Dewi (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study aims to comprehensively examine the effect of service quality and customer value on customer satisfaction, while also exploring the role of trust as a moderating variable. The focus of the research is on participants of the Digital Marketing Independent Internship at PT Satukelas Adhyapana Nusantara, Jakarta. An explanatory quantitative approach was employed, involving 87 respondents selected through purposive sampling. The collected data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS 4 software. The results indicate that both service quality and customer value have a significant positive effect on customer satisfaction. Trust was also found to have a direct effect on satisfaction. However, the moderating role of trust was significant only in the relationship between service quality and customer satisfaction. In contrast, its moderating effect on the relationship between customer value and satisfaction was found to be statistically insignificant. These findings provide empirical support for the SERVQUAL theory, the concept of customer value, and the performance-expectations model, while also reinforcing literature that highlights the importance of trust in sustaining customer relationships. From a practical standpoint, this research emphasizes the need for strategies that integrate service quality enhancement with the delivery of perceived value, accompanied by efforts to build and maintain trust as a reinforcing factor for satisfaction. This combination of strategies is expected to enhance positive customer experiences, foster loyalty, and sustain long-term relationships. Furthermore, this study offers valuable contributions for developing marketing strategies and managing customer relationships in the digital education sector, which faces increasingly intense competition and challenges in the era of technological transformation and globalization.